Unmet Needs And Missed Opportunities: A Facility-Based Analysis of Delayed Decision-Making for Safe Abortion Among Women In Northern India - Deshpande, Juhi (Universitas Andalas, 2025)
Unsafe abortion is a significant contributor to maternal mortality, particularly in resource-limited settings. Despite supportive legal frameworks, women in Northern India encounter delays in seeking safe abortion services. A facility-based cross-sectional study was conducted among 500 women seeking abortion services at three tertiary healthcare centers in Northern India. Data were collected using structured interviews and medical record reviews. Participants reported an average delay of 18 days in seeking abortion services. Lack of awareness about legal rights (42%), fear of social stigma (37%), and limited economic resources (29%) were significant contributors to delay. Rural women experienced longer delays than urban women. This study highlights critical gaps in awareness, access, and societal acceptance related to safe abortion in Northern India. To reduce delays, strengthened community education, improved referral networks, and better training for frontline healthcare providers are essential. Addressing these gaps at policy and programmatic levels can alleviate the burden of unsafe abortion and reduce preventable maternal morbidity and mortality. This study's findings have significant implications for improving maternal health outcomes in Northern India